Dinamika Psikologis dan Sosial dalam Pembentukan Minat Investasi Keuangan pada Mahasiswa - Arniman Harefa; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse the psychological and social dynamics in shaping investment interest among undergraduate Management students at STIEPARI Semarang, as well as to reveal the integrative contribution between internal and external factors in forming students’ investment intentions. The problem focuses on how motivation, financial literacy, self-efficacy, and risk perception interact with peer influence, family support, lecturers, and social media in developing investment interest. To approach this issue, the study employs the Theory of Planned Behaviour enriched with a behavioural finance perspective to explain the relationship between attitudes, subjective norms, and perceived behavioural control in the student context. Data were collected through in-depth interviews with twelve students and three supporting informants, observations, and documentation, and were analysed qualitatively using a thematic approach. The results show that investment interest is not influenced partially, but is formed through a dynamic interaction between self-efficacy and social validation that reinforce each other. The novelty of this study lies in the finding that investment experience acts as a mediating factor linking financial literacy to the development of self-confidence and risk-taking behaviour. This study concludes that students’ investment interest is a multidimensional construct influenced by the integration of psychological and social factors within the academic environment.